Resistência mecânica à penetração em latossolo vermelho após sucessivos cortes mecanizas de cana-de-açúcar - Rossini, Danilo Baldan [UNESP] (2014)
Considering the importance of sugarcane production and the intensification of machinery traffic, the aim of this study was evaluate soil mechanical resistance to penetration (SMRP) to compare the level of soil compaction in relation to ratoon cycle. The assessments of RMSP were performed after mechanical harvesting and repeated for four years in three areas cultivated with variety SP 87-365, located at Santa Izabel farm, Jaboticabal, São Paulo. An electronic penetrometer coupled to an ATV was used to measure SMRP up to 50 cm depth in two regions, near ratoon or crop row (FC) and at center of inter-row or traffic track (FR). From georeferenced data it was generated maps of spatial variability of SMRP to layers 1-10, 11-20, 21-30, 31-40 and 41-50 cm of depth that allowed visualization of the spatial distribution of SMRP values and estimate levels of compaction of each treatment and each layer in the soil profile sampled. The average SMRP values obtained varied between treatments without following a defined order according to harvest cycle and may have been influenced by the water content of the soil. There was a predominance of average values between 2 and 3 MPa. Regarding the vertical distribution in soil profile, the values of SMRP were lower in the surface layer in both regions, increasing with depth in FC, with higher levels in the 41-50 cm layer. At FR, values were higher in the 11-20 cm layer. It could be concluded that the traffic of machines caused changes in the MRSP